Are animals choosing foraging patches according to spatial scaling laws or predator avoidance arguments? : a study on grazing ungulates in Hluhluwe Imfolozi - Ballantyne, Fiona (Department of Biological Sciences, 2023)
Spatial scaling laws predict that patch choke in animals in determined by body size, with smaller animals utilising smaller patches. However, this theory does not take into consideration the potential impact predator avoidance behaviour may have on patch choice. Smaller animals are more at risk from predation; thus they have to choose grazing patches that meet their nutritional requirements without exposing themselves to an added risk of predation